SOLUBILITY OF EXCESS ALUMINA IN HYDROUS GRANITIC MELTS IN EQUILIBRIUM WITH PERALUMINOUS MINERALS AT 700-800 °C AND 200 MPA, AND APPLICATIONS OF THE ALUMINUM SATURATION INDEX - Acosta-Vigil A.; London D.; Morgan G.B.; Dewers T.A. (My University, 2003)
We have studied the controls on the Aluminum Saturation Index (ASI = molec. Al2O3/[(CaO)+(Na2O)+(K2O)]) and the concentration of normative corundum of granitic liquids saturated in alumina by equilibrating peraluminous minerals with initially metaluminous haplogranitic minimum composition liquids at 700-800 °C and 200 MPa, at, and below H2O saturation. The ASI and normative corundum increase with increasing H2O concentration in the melt (≈0.04 to 0.10 moles excess Al2O3 per mole of H2O), temperature, and with addition of the non-haplogranitic components Fe, Mg, and B. The ASI parameter and concentration of normative corundum cannot be used to monitor aAl2O3 between different mineral assemblages and melt because other components that affect the solubility of alumina, including H2O, Fe, Mg, and B, do not appear in their formulations. ASI and normative corundum, however, provide petrogenetic information about magmas generated by partial melting of strongly peraluminous protoliths by virtue of their regular and predictable variation with melt composition (e.g., H2O concentration) and temperature. For the application of these data to natural rocks it is necessary to choose as an analogue system the ASI-solubility or normative corundum-solubility relations of the most chemically complex peraluminous mineral present in the rock. Comparison of ASI values of anatectic leucosomes and allochthonous leucogranites with experimentally predicted values suggests low H2O concentrations in melt during crustal partial melting. Rapid melt segregation before equilibration with restitic peraluminous phases is also suggested in some cases.